Destination attractiveness of a theme park: Legoland Theme Park Malaysia / Murni Azila Ahmad - Ahmad, Murni Azila (2013)
Tourism in Malaysia has evolved significantly, from providing nature and heritage tourism related activities to the creation of fun and leisure related experience to cater the needs of specific market. Consequently, building theme park as one of tourism product to stimulate tourist’ fun and leisure demand were undertaken by developed countries especially emerging markets like Thailand, Indonesia, Singapore, including Malaysia. This study aimed to examine the effect of destination attributes towards visitors’ satisfaction as well as the visitors’ behavioural intentions by referring to Legoland Theme Park in Malaysia context. By using quantitative approach, the experiences of 384 visitors of Legoland were discovered. Descriptive statistic, correlation and multiple regression analysis were run to analyze the data, using Statistical Program for Social Analysis (SPSS) version 20. Through the analyses, some useful insights or predictors on the issues of visitors’ interest were obtained. Most importantly, the findings reveal that entertainment attributes contributes to high satisfaction level of the Legoland Malaysia visitors as well as the intentions to revisit and recommend in the future. However, the result of this study might not fit to be applied to other theme park related research, due to limitation of the contextual setting. The findings provide appropriate responses which believed to be important for the related authorities in continuously promoting theme park as tourism product, thus to be considered as a pioneering effort in producing research papers particularly related to theme park development in Malaysia.